SUPERBIRD - TOMLINSON, BRIAN (CAMBRIDGE :CAMBRIDGE UNIVERSITY PRESS, 1999)
A spaceship crashes on a strange planet. The only survivor, Mary Mount, is taken prisoner by an alien civilization. In time she is allowed to return to her old planet with some of her new friends. But when they arrive back at her home, the plan seems to have changed. And Mary doesn't receive the welcome she expects.
ESO12
Keywords: Ciencia ficción